Causes and Effects of Workplace Conflict in Midland Bank Ltd: A Case Study on Dhanmondi Branch - Islam, Md. Kamrul; Karim, Rezaul (International Journal of Business and Management Future, 2017)
Conflict is one of the major organizational phenomena. Where there is an employee involvement, conflict is obvious to occur. Workplace conflicts happen everywhere and ignoring them can be costly. The objectives of this research are to identify the causes and effects of workplace conflicts and also forecast the ways for the prevention of the occurrence of conflicts in future. A survey was carried out in this regard among the employees of Midland Bank Ltd., Dhanmondi Branch. According to the survey we found that it is the employees’ behavior that causes conflicts in organization. Majority of the participants in the survey agreed that the main causes of workplace conflict are the negative criticism & gossip, denying personal mistakes, jealousy, and moral corruption and using abusive language. The effects that workplace conflicts have in this organization are broken relationship (top most reason), instability and insecurity, loss of commitment to work, voluntary resignation etc. It is recommended that bank should introduce a formal system of information dissemination, manager should learn to practice delegation of authority and there should be adequate interaction and dialogue in conflict resolution.